Molecular docking and in vivo studies of liquiritin against acute myocardial infarction via TLR4/MyD88/NF-κB signaling - Zhou, Peng; Shen, An-lu; Liu, Pei-pei; Wang, Shu-shu; Wang, Liang (Italian Journal of Food Science, 2022)
Licorice (Glycyrrhiza glabra L.) is an essential herb in Chinese medicine, as well as a common ingredient in health foods and natural sweeteners. Liquiritin, the primary constituent of licorice, possesses a wide range of pharmacological and biological properties. This research aims to study the protective mechanism of liquiritin in the myocardium. The potential therapeutic efficacy of liquiritin against acute myocardial infarction (AMI) was tested using molecular docking and verified using an AMI rat model caused by the ligation of the LAD coronary artery. Molecular docking between liquiritin and toll-like receptor 4 (TLR4) and myeloid differentiation factor 88 (MyD88) was predicted using SystemsDock. Then, for experimental validation, in vivo studies were employed. Rats with the AMI model established by ligation of left anterior descending coronary artery were divided into four groups—sham group, model group, captopril group, and liquiritin group. LVSP, LVEDP, +dp/dtmax, and -dp/dtmax were detected and analyzed. HE and Masson staining were used to observe the pathological changes. The protein expressions of TLR4, MyD88, and nuclear factorκB p65 (NF-κB p65) were detected by Western blotting. Molecular docking showed that liquiritin may act on the TLR4 and MyD88, and, therefore, liquiritin was predicted to exert anti-inflammatory effects by regulating the TLR4/MyD88 signaling pathway. Liquiritin improved LVSP, +dp/dtmax, -dp/dtmax, and LVEDP levels, and alleviated pathological changes and cardiac fibrosis. Further study found that liquiritin could decrease the overexpression of TLR4, MyD88, and NF-κB, which validated the molecular docking study. Hence, liquiritin ameliorates AMI by reducing inflammation, and blocking TLR4/MyD88/NF-κB signaling. These results indicate that liquiritin as a potential compound could alleviate AMI and broaden its application.